On the resuscitation of clinical freedom - Burls Amanda (BMC, 2010)
Abstract Background This paper is a response to the suggestion by Sacristán et al that clinicians can increase their clinical freedom by undertaking individualised economic analyses that demonstrate that interventions, which at a population level do not reach conventional thresholds of cost-effectiveness, do so in particular patients. Discussion In this reply, I question the presumption that "clinical freedom" is necessarily desirable and go on to argue that, even if it is, the proposal that clinicians should do individualised economic evaluation is flawed. Firstly, the additional clinical choice that may be gained from individualised economic analyses that demonstrate that an intervention, generally considered not to be cost-effective, is cost-effective in a particular patient, is likely to be counterbalanced by other analyses that produce the converse result (i.e. that an intervention that is cost-effective at a population level may not be so in a particular patient) - a complementary consequence, which is ignored by Sacristán et al in their paper. Secondly, the skills and time required to do an individualised economic analysis are likely to exceed those of most clinicians. Thirdly, and most importantly, asking clinicians to make rationing judgements at the point of care is a threat to patient trust and can harm the doctor-patient relationship. Summary Individualised economic evaluations are neither a desirable nor feasible method for increasing clinical choice.